2010
DOI: 10.1128/aem.01784-10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Composition of the Cellulolytic Flora on the Development of Hydrogenotrophic Microorganisms, Hydrogen Utilization, and Methane Production in the Rumens of Gnotobiotically Reared Lambs

Abstract: We investigated the influence of the composition of the fibrolytic microbial community on the development and activities of hydrogen-utilizing microorganisms in the rumens of gnotobiotically reared lambs. Two groups of lambs were reared. The first group was inoculated with Fibrobacter succinogenes, a non-H 2 -producing species, as the main cellulolytic organism, and the second group was inoculated with Ruminococcus albus, Ruminococcus flavefaciens, and anaerobic fungi that produce hydrogen. The development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
6
24
0
1
Order By: Relevance
“…Based on these results, we could hypothesize that, in the present study, FO might have enhanced the growth of some rumen cellulolytic bacteria that do not produce hydrogen from their fermentations, such as Fibrobacter succinogenes. The results of Chaucheyras-Durand et al (2010) support, at least partly, this hypothesis: those authors noted that, in reared lambs, CH 4 yield was reduced (this was not the case in the present study) when the dominant fibrolytic species was Fibrobacter succinogenes (a non-H 2 -producing species). However, in the study of Chaucheyras-Durand et al (2010), fiber degradation was not impaired by the treatment (non-H 2 -vs. H 2producing rumen bacteria), whereas FO increased NDF digestibility in the present study.…”
Section: Methane Production and Rumen Fermentation Parameterssupporting
confidence: 80%
“…Based on these results, we could hypothesize that, in the present study, FO might have enhanced the growth of some rumen cellulolytic bacteria that do not produce hydrogen from their fermentations, such as Fibrobacter succinogenes. The results of Chaucheyras-Durand et al (2010) support, at least partly, this hypothesis: those authors noted that, in reared lambs, CH 4 yield was reduced (this was not the case in the present study) when the dominant fibrolytic species was Fibrobacter succinogenes (a non-H 2 -producing species). However, in the study of Chaucheyras-Durand et al (2010), fiber degradation was not impaired by the treatment (non-H 2 -vs. H 2producing rumen bacteria), whereas FO increased NDF digestibility in the present study.…”
Section: Methane Production and Rumen Fermentation Parameterssupporting
confidence: 80%
“…It has been reported that hydrogen transfer through methanogenesis is beneficial to the degradation of plant cell wall carbohydrates in the rumen (Chaucheyras-Durand et al, 2010) and the microbiota in the large intestine of pigs contains all of the predominant ruminal cellulose degrading bacteria, including F. succinogenes (intestinalis), Ruminococcus albus and Rumnococcus flavefaciens (Varel and Yen, 1997). Accordingly, we also quantified some of the abovementioned bacteria and anaerobic fungi in the large intestinal contents, but only F. succinogenes and anaerobic fungi were successfully amplified.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that, in the rumen, among the major cellulolytic communities, anaerobic fungi are the major contributors of H 2 , whereas F. succinogenes does not produce H 2 (Chaucheyras-Durand et al, 2010). Miller (1991) reported that feed ingredients rich in crude fiber stimulate some microbial species within the cellulolytic-methanogen consortium, which serve to couple the degradation of carbohydrates with the use of H 2 for the reduction of CO 2 to methane.…”
Section: Discussionmentioning
confidence: 99%
“…This hydrogen transfer is important for a good functioning of the rumen ecosystem, but at the same time methane formation represents a loss of energy (10-12% of the metabolizable energy of the host animal) and this gas being a potent greenhouse gas, it should be decreased [157]. Studies with gnotobiotically-reared lambs have shown that animals inoculated with F. succinogenes were less prone to produce methane than lambs inoculated with Ruminococci and fungi, without significant modifications of rumen fibre degradability and volatile fatty acid concentrations [158]. The use of microbial solutions to promote F. succinogenes would then appear interesting to be able to mitigate methane emissions by cattle.…”
Section: Discussionmentioning
confidence: 99%